2009
DOI: 10.1186/1476-511x-8-23
|View full text |Cite
|
Sign up to set email alerts
|

n-3 polyunsaturated fatty acids in milk is associate to weight gain and growth in premature infants

Abstract: BackgroundLinoleic 18:2 (n-6) and α-linolenic 18:3 (n-3) essential fatty acids and long-chain polyunsaturated fatty acids (LC-PUFA) are essential nutrients for growth and neonatal development. Consumption of preformed n-3 LC-PUFA has been shown to increase gestational duration and to decrease the incidence of premature birth in human studies. This study evaluated the association of essential fatty acids and LC-PUFA in breast milk on the growth of premature children (weight, height and head circumference).Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…In our study, milk AA levels were negatively associated with baby weight at 1.5 and 3.5 months and milk DHA levels were negatively associated with baby length at 3.5 months during lactation in the preeclampsia group. In contrast, few studies have shown that total milk omega 3 PUFA in normal population was positively associated with infant weight gain (Tinoco et al, 2009), motor, mental and behavioral developments (Sabel et al, 2012). A recent review discusses the controversial reports on fatty acid supplementation effects on neurodevelopment in both animal and human studies (Davis-Bruno and Tassinari, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, milk AA levels were negatively associated with baby weight at 1.5 and 3.5 months and milk DHA levels were negatively associated with baby length at 3.5 months during lactation in the preeclampsia group. In contrast, few studies have shown that total milk omega 3 PUFA in normal population was positively associated with infant weight gain (Tinoco et al, 2009), motor, mental and behavioral developments (Sabel et al, 2012). A recent review discusses the controversial reports on fatty acid supplementation effects on neurodevelopment in both animal and human studies (Davis-Bruno and Tassinari, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that docosahexaenoic acid (DHA, 22:6n-3) is important for, e.g., visual development in infancy (5), but it is presently unknown to what extent n-3 LCPUFA should be considered relevant with respect to adiposity. The natural content of n-3 PUFA in breast milk has been found to be positively associated with infant weight gain in preterm (6) but not term-born infants (7). Furthermore, two intervention studies giving n-3 LCPUFA to pregnant and/or lactating mothers suggest a programming effect on later infant BMI, although in opposite directions (8,9).…”
mentioning
confidence: 99%
“…Finally, higher colostrum levels of n‐6 fatty acids corresponded to the increased risk of rhinitis . Furthermore, the PUFA profile was proved to modulate both the growth rate of preterm newborns and the mental development of all infants .…”
Section: Discussionmentioning
confidence: 97%